The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1074/mcp.m113.030643
|View full text |Cite
|
Sign up to set email alerts
|

Interlaboratory Study on Differential Analysis of Protein Glycosylation by Mass Spectrometry: The ABRF Glycoprotein Research Multi-Institutional Study 2012

Abstract: One of the principal goals of glycoprotein research is to correlate glycan structure and function. Such correlation is necessary in order for one to understand the mechanisms whereby glycoprotein structure elaborates the functions of myriad proteins. The accurate comparison of glycoforms and quantification of glycosites are essential steps in this direction. Mass spectrometry has emerged as a powerful analytical technique in the field of glycoprotein characterization. Its sensitivity, high dynamic range, and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
94
1
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 105 publications
(99 citation statements)
references
References 48 publications
3
94
1
1
Order By: Relevance
“…This was rather surprising, because a recent inter laboratory study by Leymarie et al, revealed for the common approaches used in glycoproteomics rather strong deviations in their quantitative as well as qualitative results between different laboratories (71).…”
Section: Rp-esi-ms and Rp-microarray-maldi-ftms Revealed Very Similamentioning
confidence: 98%
“…This was rather surprising, because a recent inter laboratory study by Leymarie et al, revealed for the common approaches used in glycoproteomics rather strong deviations in their quantitative as well as qualitative results between different laboratories (71).…”
Section: Rp-esi-ms and Rp-microarray-maldi-ftms Revealed Very Similamentioning
confidence: 98%
“…GlycoWorkbench was additionally employed (http://www.eurocarbdb.org/applications/ms-tools) to assist in assigning the glycan structure using in silico fragmentation analysis. The distribution of N-glycans of WT and glycosylation variants of HBsAgS was mapped using the MS signal strength of the observed N-glycan structures as an estimate of their relative abundances (58,59). This was performed using the areas of the extracted ion chromatograms (EIC) of all the charge states in which the identified N-glycans appeared.…”
Section: Pgc-lc-esi-ms/ms Characterization Of N-glycansmentioning
confidence: 99%
“…InstantABlabeled glycans were then analyzed by UPLC-FLR using a Waters BEH-Glycan Separations Technology column (1.7 mm, 150 £ 2.1 mm, part number 180064742) with an increasing ammonium formate gradient (mobile phase A: Acetonitrile; mobile phase B: 100 mM Ammonium formate at pH 4.4) over 60 min. An injection volume of 1 ml aqueous and a column temperature of 35 C were used; glycans were detected at a wavelength of 330 nm with an excitation wavelength of 278 nm. Peaks were integrated using Empower Ò software (Waters Corp.), and relative glycan compositions were calculated.…”
Section: Hilic(iab)mentioning
confidence: 99%
“…In principle the methods can be sub-divided into 3 categories: 3,[21][22][23] (1) Analysis of the IgG molecule with electrospray ionization mass spectrometry (ESI-MS)-either on the intact molecule after reduction of disulphide bonds, or after a limited digestion with a proteolytic enzyme and deduction of the overall glycan composition; [24][25][26] (2) Enzymatic release of the Fc glycans and measurement with mass spectrometric methods, by HPLC with pulsed amperometric detection or by capillary electrophoresis (CE)/ HPLC-based methods after fluorescent labeling; 27,28 and (3) Proteolytic cleavage of the IgG molecule and analysis of the glycopeptides with matrix-assisted laser desorption/ionization-mass spectrometry (MALDI-MS) or electrospray ionization-mass spectrometry ESI-MS. [29][30][31][32] Comparisons of different methods for analysis of IgG Fc-glycosylation have been reported, but these studies included a limited number of methods or compared mainly mass spectrometry-based methods. [33][34][35][36][37][38] Thus, a thorough comparison of different methods for glycoanalysis is still lacking.…”
Section: Introductionmentioning
confidence: 99%